Chromosome aberrations in workers occupationally exposed to tritium - Tawn, E Janet; Curwen, Gillian B; Riddell, Anthony E (Journal of radiological protection, 2018)
This paper reports the findings of an historical chromosome analysis for unstable aberrations, undertaken on 34 nuclear workers with monitored exposure to tritium. The mean recorded β-particle dose from tritium was 9.33 mGy (range 0.25-79.71 mGy) and the mean occupational dose from external, mainly γ-ray, irradiation was 1.94 mGy (range 0.00-7.71 mGy). The dicentric frequency of 1.91 0.53 × 10−3 per cell was significantly raised, in comparison with that of 0.61 0.30 × 10−3 per cell for a group of 66 comparable worker controls unexposed to occupational radiation. The frequency of total aberrations was also significantly higher in the tritium workers. Comparisons with in vitro studies indicate that at these dose levels an increase in aberration frequency is not expected. However, the available historical tritium dose records were produced for the purposes of radiological protection and based on a methodology that has since been updated, so tritium doses are subject to considerable uncertainty. It is therefore recommended that, if possible, tritium doses are reassessed using information on historical recording practices in combination with current dosimetry methodology, and that further chromosome studies are undertaken using modern FISH techniques to establish stable aberration frequencies, as these will provide information on a cumulative biological effect.